Feedback from the European Bioanalysis Forum: focus workshop on current analysis of immunogenicity: best practices and regulatory hurdles. (February 2018) - Goodman, Joanne; Cowen, Simon; Devanarayan, Viswanath; Egging, David; Emrich, Thomas; Golob, Michaela; Kramer, Daniel; McNally, Jim; Munday, James; Nelson, Robert; Pedras-Vasconcelos, João A; Piironen, Timo; et al.
European Bioanalysis Forum Workshop, Lisbon, Portugal, September 2016: At the recent European Bioanalysis Forum Focus Workshop, 'current analysis of immunogenicity: best practices and regulatory hurdles', several important challenges facing the bioanalytical community in relation to immunogenicity assays were discussed through a mixture of presentations and panel sessions. The main areas of focus were the evolving regulatory landscape, challenges of assay interferences from either drug or target, cut-point setting and whether alternative assays can be used to replace neutralizing antibody assays. This workshop report captures discussions and potential solutions and/or recommendations made by the speakers and delegates.